J’ai l’impression d’être la seule à aimer l’allemand » : Perceptions et représentations d’étudiants face à leur apprentissage de l’allemand en Alsace - Faucompré, Chloé; Putsche, Julia (Glottodidactica, 2022)
This contribution proposes a reflection on the representations and perceptions that Alsatian students have of their German language learning in the context of the Upper Rhine. After explaining the challenge of teaching and learning German in this cross-border context, we will present some significant quantitative and qualitative results in order to establish a sort of diagnosis of the decline in bilingualism observed by interregional institutions.